Parents’ Speech in the NICU and Language Development of Very Preterm Children at 12 and 24 Months - Anette Aija, MD; Eva Ståhlberg-Forsén, PhD; Liis Toome, MD, PhD; Laura Aarnos, MS, MB; Sari Ahlqvist-Björkroth, PhD; Suvi Stolt; Liisa Lehtonen (Journal of Pediatrics: Clinical Practice, 2025)
Objective: It is unclear if speech input in neonatal units improves delayed language development in very preterm infants. This longitudinal study investigated whether the parents’ speech in family-centered neonatal units associated with language outcomes in children born very preterm. Study design: The auditory environment of 82 infants born <32 gestational weeks was recorded using Language Environment Analysis at 32–34 weeks of postmenstrual age. The language environment was analyzed for the total recording time and the periods when the parents were present. Receptive and expressive language skills were measured at 1 year (MacArthur-Bates Communicative Development Inventory) and 2 years of corrected age (Reynell Developmental Language Scales III). Results: Father's word frequency on recording day (b ln-scale 0.05, 95% CI 0.003–0.09, P = .04), and conversational turns with the mother during 14 days (b ln-scale 0.08, 95% CI 0.01–0.16, P = .03) were positively associated with expressive lexicon size at 1 year. Overall adult word frequency was negatively associated with the child's expressive language skills at 2 years of corrected age (b in-scale −0.13, 95% CI -0.24–-0.01, P = .03). Conclusions: Parents’ speech in the neonatal unit may support language development of children born preterm, whereas high total adult words - including the time when parents were not present in the unit - may impair it. Our findings should be cautiously interpreted as the associations were weak. Trial registration: Auditory Environment by Parents of Preterm Infants (APPLE), registration number: NCT04826978, date of registration: 2021-03-29.